Photocatalytic degradation of Orange II dye using Zeolite X-Fe catalyst synthesized from coal fly ash (2016)
Abstract. The degradation of Orange II dye (OII) by a heterogeneous photoFenton process using Fe catalysts supported on zeolite was studied. Zeolite X was synthesized by hydrothermal treatment from fly ash, which is a solid waste from the thermoelectric company, Termotasajero S.A, located in Norte de Santander. The reported synthesis methodology was optimized, evaluating aging and time of hydrothermal treatment. The synthetic zeolite, with high BET surface area, was modified by a impregnation process to deposite different amounts of iron. Iron nitrate nonahydrated, Fe(NO3)3.9H2O, was the precursor salt and the prepared catalyst had 8.1 wt% y 10.3 wt% of Fe. The support and catalysts were characterized by Xray diffraction (XRD), N2 adsorption/desorption, X-ray fluorescence (XRF), Thermogravimetric analysis (TGA) and Scanning Electron Microscopy (SEM). The effect of the initial concentrations of OII and H2O2, and the iron load in the support on the degradation rate of OII was investigated by carrying out experiments in a batch reactor and to a fixed pH value. The experiments were carried out according to an experimental response surface design and the OII concentration histories (i.e., concentration evolution along reaction time) were studied by UV spectrophotometry at a wavelength of 486 nm. The dye photodegradation was described by a simple semi-empirical kinetic model, based on the Fermi’s equation. The model was fitted to the dye concentration histories, being the kinetic parameters determined by nonlinear regression. The catalysts showed very good catalytic performances, with color degradations degrees as high as 90% after 3 hours. The initial concentration of OII was the most influential variable in the dye degradation and the iron leaching from the support was negligible, allowing the use of the catalyst in consecutive reaction cycles. The contribution in color photodegradation due to the presence of 1 wt% TiO2 was investigated.